A Scoping Review of Assertiveness Therapy for Reducing Bullying Behavior and Its Impacts Among Adolescents - Iyus, Yosep; Suryani, Suryani; Henny Suzana, Mediani; Ai, Mardhiyah; Indra, Maulana; Taty, Hernawaty; Helmy, Hazmi (Dove Medical Press Limited, 2024)
: Bullying is a global problem in adolescents which has increased every year. One of the factors in the occurrence of bullying is the ability of interpersonal skills. This ability can build good relationships with assertive between adolescents and can prevent bullying. The purpose of this study is to describe assertiveness therapy for reducing bullying behavior and its impacts among adolescents. The method used in this study is scoping review. The search strategy used is PRISMA Extension for Scoping Reviews through three databases namely PubMed, CINAHL, and Scopus. The authors used inclusion criteria and exclusion criteria in the selection of articles. The major keywords used in the article search were bullying, assertiveness therapy, and adolescents. Data analysis used descriptive qualitative. The results showed that there were 10 articles that discussed assertive therapy. All articles show that assertiveness therapy can reduce bullying behavior and its impact significantly, such as reducing the impact of anxiety and increasing self-esteem. Assertiveness therapy methods carried out in the form of education, games, and role play. Education is carried out online and offline. Educational media is provided directly and through media such as educational videos which can be accessed at any time. Gender and cultural approaches are important aspects in the implementation of assertive therapy. Assertive therapy can improve interpersonal skills, social skills, empathy and assertiveness so that it can reduce bullying behavior and its impacts in adolescents. Then, this data becomes the basis for nurses to carry out assertive therapy as an effort to prevent and reduce bullying behavior in adolescents.